INTERPREGNANCY INTERVAL AND PREECLAMPSIA AMONG PREGNANT WOMEN: A HOSPITAL-BASED CASE CONTROL STUDY IN INDONESIA - Desvita Fitrianti; Eko Mardiyaningsih (Universitas Kusuma Husada Surakarta, 2026)
Background: Preeclampsia remains a major maternal health problem because of its contribution to maternal and perinatal morbidity and mortality. Interpregnancy interval is an important obstetric factor that may affect maternal physiological recovery and adaptation to subsequent pregnancies. This study aimed to analyze the association between interpregnancy interval and the incidence of preeclampsia among pregnant women.Methods: A quantitative, observational, case-control study was conducted using medical record data from pregnant women registered between January and December 2025. The sample comprised 66 respondents: 33 with preeclampsia (case group) and 33 without preeclampsia (control group). Data were collected using a structured checklist and analyzed using univariate and bivariate methods. The Chi-square test and Odds Ratio (OR) were applied at the 0.05 significance level.Results: Most respondents in both groups were within the non-risk reproductive age range and were multiparous. Risky interpregnancy intervals were found in 87.9% of women with preeclampsia and 21.2% of women without preeclampsia. Statistical analysis showed a significant association between interpregnancy interval and preeclampsia incidence (p < 0.001). Women with risk interpregnancy intervals had a higher likelihood of developing preeclampsia than those with non-risk intervals (OR = 6.042; 95% CI: 2.393–15.256).Conclusion: Interpregnancy interval is significantly associated with the occurrence of preeclampsia. These findings emphasize the importance of pregnancy planning, postpartum family planning counseling, and antenatal risk screening to reduce maternal complications related to preeclampsia.